Nanomedicine in otorhinolaryngology future prospects Nanomedizin in der HNO-Heilkunde ein Ausblick - Dürr, Stephan; Tietze, Rainer; Lyer, Stefan; Alexiou, Christoph (Laryngo-Rhino-Otologie, 2012)
Nanomedicine in Otorhinolaryngology Future Prospects Background: Nanotechnology becomes more and more important in the world of today. Equally, it does generally in medicine and of course specifically in otorhinolaryngology. Essentially, there are the following fields: Diagnostics, new therapies and agents, drug delivery and medical implants. Material and Methods: An extensive literature research on nanomedicine in otorhinolaryngology was carried out in the standard online medical reference databases PubMed/Medline and Web of Science. Furthermore, we are giving an overview of the work of the Department of Otorhinolaryngology, Head and Neck Surgery, Section of Experimental Oncology and Nanomedicine (SEON), University Hospital Erlangen. Results: A lot of new and innovative studies on nanotechnology in diagnostics and therapy were recovered. Depending on the variety in otorhinolaryngology, there are numerous versatile approaches, according to the different areas. The main part is engaged in drug delivery. Conclusions: The efforts to exploit the potential of nanotechnology in otorhinolaryngology are multifaceted, innovative and seminal. The best perspective of success is attributed to nanoparticulate drug delivery systems. © Georg Thieme Verlag KG Stuttgart . New York.
CRIS-Team Scopus Importer:2022-06-27
Keywords: drug delivery; magnetic drug targeting; nanomedicine; nanoparticles; otorhinolaryngology